Green finance and foreign direct investment–environmental sustainability nexuses in emerging countries: new insights from the environmental Kuznets curve - Qadri, Syed Usman; Shi, Xiangyi; Rahman, Saif ur; Anees, Alvena; Ali, Muhammad Sibt E.; Brancu, Laura; Nayel, Ahmad Nabi (Frontiers in Environmental Science, 2023)
The primary objective of the present study is to identify the asymmetric relationship between green finance, trade openness, and foreign direct investment with environmental sustainability. The existing research utilizes the asymmetric approach to evaluate annual data from 1980 to 2021. The findings of this study show heterogeneous results. Therefore, the outcomes of the study confirm the nonlinear (NARDL) association between the variables in Pakistan. Moreover, the study describes the positive shock of foreign direct investment (FDI) as a significant and positive relationship with environmental degradation, while the negative shock of FDI shows a negative and significant relationship with the environment. Furthermore, the study scrutinizes the positive shock of green finance as a significant and negative relationship with environmental degradation; the negative shocks also show a negative relationship with environmental degradation in Pakistan. In addition, the consequences of the study suggest that the government should implement taxes on foreign investment and that investors should use renewable energy to produce goods. Furthermore, the results suggest that the government should utilize fiscal policy and fiscal funds to enhance carbon-free projects. Moreover, green securities should be used for green technologies. However, Pakistan can control its carbon emissions and achieve the target of a sustainable environment. Therefore, Pakistan’s government should stabilize its financial markets and introduce carbon-free projects. Furthermore, the main quantitative achievement according to the outcomes suggests that policymakers make policies in which they suggest to the government to control foreign investment that causes carbon emissions because of trade openness and also invest the funds in renewable energy, which helps to control the carbon emissions.